Performance Evaluation of a Solar Assisted Dual Condenser Heat Pump System for Drying of Pandan Leaves (Pandanus Amaryllifolius) - Rohaimi Abdullah; Adnan Ibrahim; Muhammad Amir Aziat Ishak; Kamaruzzaman Sopian; Hasila Jarimi; Halim Razali; Ghaith Abusaibaa (Penerbit Universiti Kebangsaan Malaysia, 2025)
The solar-assisted heat pump drying (SAHPD) system uniquely incorporates solar-heating refrigerant through hot water from solar evacuated tubes, offering distinct advantages. This study analyzed three experimental setups: a heat pump dryer (HPD) without solar assistance, SAHPD configuration 1 (C1-SAHPD) with solar-heated refrigerant at the discharge line, and SAHPD configuration 2 (C2-SAHPD) with solar-heated refrigerant between condensers, both for performance and economic viability. The experiments maintained consistent parameters, including 5.5 kg of Pandan leaf (Pandanus amaryllifolius), an airfl ow rate of 0.135 kg/s, and a refrigerant operating pressure of 9.65 bar. The SAHPDs operated when the hot water temperature in the storage tank reached between 70°C and 90°C, with a daily average radiation intensity ranging from 0.670 to 1.102 kW/m² for heating the water. The study revealed average coefficients of performance (COPavg ) of 5.34, 5.43, and 6.53 for HPD, C1-SAHPD, and C2-SAHPD, respectively. The specifi c moisture extraction rate (SMER) for HPD was 2.64, while C1-SAHPD and C2-SAHPD had SMERs of 1.88 and 2.71 at solar fractions of 0.34 and 0.45, respectively. Notably, C2-SAHPD reduced electricity consumption by 46%. The payback period for drying 11 kg of Pandan leaves per day was 4.56 months for HPD, 4.32 months for C1-SAHPD, and 3.84 months for C2-SAHPD. The study concluded that C2-SAHPD was the most efficient dryer system for Pandan leaves based on its higher efficiency, SMER, and cost recovery. Additionally, the performance optimization presented in this study contributed to developing a novel technique for classifying dryer technologies.